Synthesis of novel low‐cost porous gangue microsphere/geopolymer composites and their adsorption properties for dyes. Issue 6 (20th June 2018) - Yan, Shu; He, Peigang; Jia, Dechang; Wang, Qinggang; Liu, Jingjing; Yang, Jinlong; Huang, Yong
Abstract: A novel porous coal gangue microsphere/geopolymer (CG/KGP) composite was firstly synthesized by adding gangue microspheres into geopolymer matrix. Effects of precalcined temperature of CG microspheres on the microstructure and specific surface area of the porous CG/KGP particles were systematically investigated. Adsorption properties of the CG/KGP composites were also reported. Results showed that the CG/KGP composites contained mainly amorphous phase and many functional groups were on the particle surface. The precalcined CG microspheres were dispersed homogenously and bonded well with the KGP matrix. The CG900/KGP samples showed better adsorption properties than the pure KGP. As for the dosage of 4 g/L (starting concentration, 100 mg/L), adsorption capacity achieved the highest value of 24.6 mg/g and the removal efficiency reached 98%. Adsorption of MB onto CG900/KGP particles followed the pseudo‐second‐order kinetic model. The novel porous CG/KGP composite has potential application in wastewater filtration and adsorption treatment. Abstract : Preparation procedure and adsorption of MB for CG/KGP particles.